Category of negation paradigm in diachrony - Pasichnyk, Nataliia; Hotsa, Nataliia; Kosenko, Anna; Plavutska, Olga; Bloshchynskyi, Ihor (Linguistics and Culture Review, 2021)
The negation in logic and linguistics, negation as a grammatical category on the morphological and syntactic levels are substantiated in the article. It is concluded that in broad semantic terms negation can be expressed in morphologic and syntactic ways in natural language. On the morphological level, negative affixes paradigm and separate parts of speech are taken into consideration, while on the syntactic level the whole negative sentence that includes one or more than one negator is observed. Negation is expressed using affixes that have explicative and implicative components in their meaning. Authentic affixes preserve the semantic meaning of the words they etymologically derive from, giving the word they join to, a special shade of negation. The main source of enrichment of the negative affixes paradigm and their new meaning are affixes borrowed from other languages. The study of the category of negation on different levels in diachronic aspects can help to observe the development of particular parts of speech, which can express negation, and serve as a base for further studies of negation in the different discourses and communicative situations.